(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the theme of love in the poetry of the poet E.Vakhidov. In particular, the interpretation of the image of the lover and the lover reveals the unique spiritual world of the lyrical hero. The leading position of the theme of love in the work of the famous poet has been thoroughly analyzed. The important role of the symbol of the lover as an enthusiastic, fierce and active fighter of social and domestic life is proved by vivid poetic examples. In particular, the poetic lines of the poet Irik’s hero in the form of a lover, high human qualities such as loyalty to the neighbor, loyalty, and kindness are widely covered in accordance with the content of the artistic text. In general, through the article, it is possible to find answers to the questions about the concept of love, the specific characteristics of the character of the lyrical hero - the lover, and the beautiful moral world of the lover in the works of E. Vahidov.